Analisis Keterampilan Memahami dalam Surat dan Laporan Bahasa Arab di Madrasah Nurul Istifadah - Rif'atus Surur; Rofiq Ainur Sofa (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
This study aims to analyze the skills of understanding Arabic letters and reports at Madrasah Nurul Istifadah and identify factors that influence students' understanding, the learning methods used, and the effectiveness of the strategies applied. Understanding skills in this context include the ability to recognize text structure, analyze content, and interpret formal language styles. The study used a qualitative descriptive approach with data collection methods in the form of observation, interviews, and documentation. The results of the study showed that group discussion strategies and repeated reading with gradual understanding proved effective in improving students' understanding of Arabic letters and reports. This strategy not only improves students' linguistic abilities, but also encourages cooperation, self-confidence, and critical thinking skills. This study is expected to contribute to the development of more contextual and effective Arabic language learning methods, especially in understanding formal texts.